(untitled) (Latakia University Journal -Medical Sciences Series, 2022)
Introduction: The current lack of a reliable, inexpensive tool to predict treatment response in newly diagnosed Multiple Myeloma (MM) patients poses an urgent need, especially in resource-limited countries. Gamma Gap (GG) represents the measured difference between serum total protein and albumin on conventional chemistry panel. Methods: We prospectively studied 53 newly diagnosed MM patients, who were admitted to the Cancer Treatment Center in Tishreen University Hospital in Latakia between July 2019 and July 2021, in order to determine the value of GG in predicting treatment response after first-line therapy. Results: There was a strong linear correlation between GG and M-spike at diagnosis, at midpoint, and after treatment with r:0.89, 0.91, and 0.85, respectively, and p<0.01. ΔGG and ΔM-spike after treatment were also strongly correlated at p<0.01. ΔGG% had a clear predictive value of response after first-line therapy with an OR=1.2 and p<0.001. We were able to set a cut-off value of ΔGG% at 73% that determines the optimal response after first-line therapy, with a sensitivity of 79% and a specificity of 71%. Conclusion: GG, measured through conventional metabolic chemistry panel, can be used as a reliable and readily available tool to estimate M-spike at different points throughout treatment. It can also help predict treatment response in patients with newly diagnosed MM.